Biosurfactant and soil wetting bacteria amendments for enhancing water retention in agricultural soils - Gutierrez, Moises Maldonado (My University, 2025)
Climate-driven drought and rising global population are driving increased demand for freshwater resources, particularly in agriculture. In the U.S. Central High Plains, irrigation increasingly relies on the rapidly depleting Ogallala Aquifer, highlighting the urgent need for sustainable soil and water management strategies. This dissertation investigates a microbial and biochemical approach to improving soil water retention, focusing on the biosurfactant-producing bacterium Bacillus subtilis and its secondary metabolite, surfactin. These agents offer a potentially sustainable, environmentally responsible approach to soil treatment in order to eliminate soil water repellency, enhance water retention, and improve agricultural water use efficiency, particularly in arid and semi-arid climates. The research begins by reviewing the physicochemical basis of soil hydrophobicity, a key limitation to water infiltration and availability. The literature identifies amphiphilic organic compounds as a primary contributor to water-repellent soil, which becomes more pronounced under dry conditions. While synthetic surfactants can be added to the soil to transition these hydrophobic layers to hydrophilic layers, their environmental and economic drawbacks have prompted interest in microbially-produced biosurfactants like surfactin, which have high surface activity, low toxicity, and are stable under diverse conditions. The effect of soil texture in response to surfactin treatment is first presented. Soil textures were systematically varied by mixing sand and silty clay loam soils together at varied ratios, achieving mineralogically equivalent soils with a range of different textures. Contact angle measurements and dryout experiments revealed that soils with sandy loam textures, where water retention is often most problematic, were most responsive with respect to water retention improvement in lab-scale studies. Next, two delivery methods are discussed: (1) direct application of surfactin and (2) indirect delivery via B. subtilis inoculation. The findings demonstrate that B. subtilis inoculation can also reduce contact angles and enhance soil water retention. Experimental data and system dynamics modeling are combined to show that treated soils retain moisture longer, reduce evaporation under dry conditions, and maintain water availability through rainy cycles. Finally, the impact of amending the soil with nitrogen-based soil enrichments, such as NH₄NO₃, to further promote B. subtilis-mediated soil water retention is reported in Chapter 5. The final portion of this thesis describes the stable encapsulation of B. subtilis in polyethylene glycol (PEG) based hydrogels. This technique has the potential to enhance bacterial survival by forming a protective barrier around cells and to enhance biosurfactant production by localizing bacterial together. Bacteria encapsulation into PEG-based hydrogels was investigated for different step-growth polymerization chemistries that use Michael-type addition reactions for hydrogel crosslinking and PEG monomers of varied molecular weights. The survival and morphology of bacteria within the hydrogels were found to be dependent on crosslinking chemistry and monomer size. Microscopic analysis showed that thiol-acrylate crosslinking chemistries were most conducive to cell viability and single-cell encapsulation and that smaller mesh sizes also favored single-cell encapsulation. Other crosslinking chemistries favored encapsulation of aggregated cells and lower cell viability. These biohybrid systems have the potential to offer controlled and sustained microbial activity in various environments, including the soil. In summary, this research advances bioinoculants towards the goal of improving water use efficiency in agriculture. While further field validation is needed, particularly with respect to biosurfactant production kinetics and soil microbiome interactions, this work lays a foundation for integrating microbial inoculants into sustainable, climate-resilient agricultural practices that can advance global food supply and freshwater security.
Keywords: Bacillus subtilis; Surfactin; Soil water retention; Evaporation rate; Hydrogels; Bacteria encapsulation